2018
DOI: 10.1155/2018/4869680
|View full text |Cite
|
Sign up to set email alerts
|

Rosai-Dorfman Disease: Self-Resolving Unilateral Lymphadenopathy and a Brief Review of Literature

Abstract: Rosai-Dorfman disease (RDD), also known as sinus histiocytosis with massive lymphadenopathy (SHML), is a disease of histiocytic proliferation with no known pathogenesis. This disease is defined by histological and cytological characteristics, including emperipolesis and positive S100 and CD68 markers. Although the disease typically presents clinically with massive bilateral lymphadenopathy due to sinus expansion from excessive histiocytosis, only unilateral lymphadenopathy was observed in this patient. The cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 14 publications
2
16
1
Order By: Relevance
“…The mechanism of histiocytic proliferation in infectious etiology is not well known. Some authors suggested that macrophage colony-stimulating factor (M-CSF) stimulates macrophages which lead to macrophages/ histiocytic proliferation [4,6]. On the other hand, autoimmune reaction can cause an acquired internal dysregulation which results in disturbance of cellular apoptotic signaling pathway mechanism that lead to macrophages/ histiocytic proliferation [5].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The mechanism of histiocytic proliferation in infectious etiology is not well known. Some authors suggested that macrophage colony-stimulating factor (M-CSF) stimulates macrophages which lead to macrophages/ histiocytic proliferation [4,6]. On the other hand, autoimmune reaction can cause an acquired internal dysregulation which results in disturbance of cellular apoptotic signaling pathway mechanism that lead to macrophages/ histiocytic proliferation [5].…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis include benign lymphoid hyperplasia with sinus histiocytosis which will lack the emperipolesis seen in RDD, Langerhans cell histiocytosis in which the cells are positive for S100, langerin, and CD1a. Other differentials include leprosy infection, rhinoscleroma, melanoma, and metastatic carcinoma [1,4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations